Digitalisasi Perpustakaan Institut Agama Islam Negeri Madura Sebagai Upaya Pemenuhan Layanan Pemustaka Sejak Pandemi COVID-19 - Albaburrahim Albaburrahim; Qori' Wahyudi (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This paper describes efforts to digitize various library services at IAIN Madura in fulfilling user services during a pandemic. The surge in Covid-19 resulted in less-than-optimal library services, even to the point of temporarily closing face-to-face services. This, of course, requires the library to make a variation so that the service remains optimal during a pandemic. One of them is maximizing digital services which are very urgent to be carried out quickly and precisely, so that users can still get library services. This issue was raised, namely how the Madura IAIN library is able to provide digital services to fulfill user services since the Covid-19 pandemic. This research was conducted using qualitative methods with data collection techniques by observation and interviews. The data analysis was carried out descriptively and interpretively based on the latest digital services as well as digital services that are experiencing the process of developing digital library applications at IAIN Madura. The results of this research are the latest digital-based library services and the development of digital applications to serve users since the Covid-19 pandemic. The newest digital library service at IAIN Madura is a digital self-lending service. Meanwhile, digital services that are undergoing application development include e-book, repository, and e-theses services. As for efforts to fulfill user services through library digitization, namely consolidating information technology (IT) teams, developing application programs, and adding library application programs to the IAIN Madura. All of these digital services are very important to be accessible and enjoyed by users during the pandemic and after the Covid-19 pandemic. This is because users still get maximum service with these digital services.